Effects of a home-based, exergaming intervention on physical function and pain after total knee replacement in older adults: a randomised controlled trial - Ari Heinonen; Raija Korpelainen; Hannu Kautiainen; Juha Paloneva; Konsta Pamilo; Timo Jämsä; Niina Katajapuu; Hannes Keemu; Maarit Janhunen; Airi Oksanen; Mikko Karvonen; Mika Luimula; et al. (BMJ Open Sport & Exercise Medicine, 2023)
Objectives To investigate the effects of 4 months of customised, home-based exergaming on physical function and pain after total knee replacement (TKR) compared with standard exercise protocol.Methods In this non-blinded randomised controlled trial, 52 individuals aged 60–75 years undergoing TKR were randomised into an exergaming (intervention group, IG) or a standard exercising group (control group, CG). Primary outcomes were physical function and pain measured before and after (2 months and 4 months) surgery using the Oxford Knee Score (OKS) and Timed Up and Go (TUG) test. Secondary outcomes included measures of the Visual Analogue Scale, 10m walking, short physical performance battery, isometric knee extension and flexion force, knee range of movement and satisfaction with the operated knee.Results Improvement in mobility measured by TUG was greater in the IG (n=21) at 2 (p=0.019) and 4 months (p=0.040) than in the CG (n=25). The TUG improved in the IG by −1.9 s (95% CI, −2.9 to −1.0), while it changed by −0.6 s (95% CI −1.4 to 0.3) in the CG. There were no differences between the groups in the OKS or secondary outcomes over 4 months. 100% of patients in the IG and 74% in the CG were satisfied with the operated knee.Conclusion In patients who have undergone TKR, training at home with customised exergames was more effective in mobility and early satisfaction and as effective as standard exercise in pain and other physical functions. In both groups, knee-related function and pain improvement can be considered clinically meaningful.Trial registration number NCT03717727.